PRÁTICAS RELIGIOSAS, CORPO E ESTILOS DE VIDA: UMA ANÁLISE COMPARATIVA ENTRE EVANGÉLICOS NO BAIRRO RUDGE RAMOS EM SÃO BERNARDO DO CAMPO - Carvalho, Williani de Almeida (2010)
This research analyzes the body as part of a process of social construction and seeks to understand the implications of the relationship between the social construction of body and evangelical religious practices. Chooses the Congregation Christian Churches, Presbyterian and Reborn in Christ in the neighborhood of Rudge Ramos, Sao Bernardo do Campo, as an investigation of this issue. This relationship is shrouded in intentions and physical manifestations involving religious practices and lifestyles of people who attend these names in the neighborhood in question. The study developed a mapping of physical techniques that mean the way people are "worth" of their bodies. When assessing the social, cultural and economic factors related to the neighborhood in question, and inserted it to the churches, we seek to understand how these three gospel traditions develop differentiated body techniques. Also, if people who attend these churches suffer any influence of the "model" of embodiment of society today is to claim that the quest for social mobility and the conditions of consumption linked to the body.(AU)